Macrophage traits in cancer cells are induced by macrophage-cancer cell fusion and cannot be explained by cellular interaction. Issue 1 (December 2015) - Shabo, Ivan; Midtbö, Kristine; Andersson, Henrik; Åkerlund, Emma; Olsson, Hans; Wegman, Pia; Gunnarsson, Cecilia; Lindström, Annelie
Abstract Background Cell fusion is a natural process in normal development and tissue regeneration. Fusion between cancer cells and macrophages generates metastatic hybrids with genetic and phenotypic characteristics from both maternal cells. However, there are no clinical markers for detecting cell fusion in clinical context. Macrophage-specific antigen CD163 expression in tumor cells is reported in breast and colorectal cancers and proposed being caused by macrophages-cancer cell fusion in tumor stroma. The purpose of this study is to examine the cell fusion process as a biological explanation for macrophage phenotype in breast. Methods Monocytes, harvested from male blood donor, were activated to M2 macrophages and co-cultured in ThinCert transwell system with GFP-labeled MCF-7 cancer cells. MCF7/macrophage hybrids were generated by spontaneous cell fusion, isolated by fluorescence-activated cell sorting and confirmed by fluorescence microscopy, short tandem repeats analysis and flow cytometry. CD163 expression was evaluated in breast tumor samples material from 127 women by immunohistochemistry. Results MCF-7/macrophage hybrids were generated spontaneously at average rate of 2 % and showed phenotypic and genetic traits from both maternal cells. CD163 expression in MCF-7 cells could not be induced by paracrine interaction with M2-activated macrophages. CD163 positive cancer cells in tumor sections grew in clonal collection and a cutoff point >25 % of positive cancer cells was significantly correlated to disease free and overall survival. Conclusions In conclusion, macrophage traits in breast cancer might be caused by cell fusion rather than explained by paracrine cellular interaction. These data provide new insights into the role of cell fusion in breast cancer and contributes to the development of clinical markers to identify cell fusion.